2001
DOI: 10.1152/ajpheart.2001.281.6.h2456
|View full text |Cite
|
Sign up to set email alerts
|

Afferent baroreceptor discharge in pregnant rats

Abstract: The baroreflex function curve is shifted to lower operating pressures, efferent sympathoexcitatory responses are attenuated, and sympathoinhibitory responses are potentiated in pregnant compared with virgin rats. It has been proposed that during pregnancy, elevated levels of 3 alpha-hydroxy-dihydroprogesterone (3 alpha-OH-DHP), a major metabolite of progesterone, may contribute to this difference, because acute intravenous administration of 3 alpha-OH-DHP to virgin female rats mimics the effects of pregnancy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
18
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
6
18
0
Order By: Relevance
“…Thus chronic administration of pregnan suppresses the response of HF atrial receptors to distension of the venoatrial junction, i.e., it mimics the effect of pregnancy on atrial volume receptor discharge. The inability of acutely administered pregnan to alter the discharge characteristics of the atrial volume receptors is consistent with the observation that this treatment also fails to modulate afferent arterial baroreceptor discharge (10).…”
Section: Discussionsupporting
confidence: 84%
“…Thus chronic administration of pregnan suppresses the response of HF atrial receptors to distension of the venoatrial junction, i.e., it mimics the effect of pregnancy on atrial volume receptor discharge. The inability of acutely administered pregnan to alter the discharge characteristics of the atrial volume receptors is consistent with the observation that this treatment also fails to modulate afferent arterial baroreceptor discharge (10).…”
Section: Discussionsupporting
confidence: 84%
“…Previously our laboratory demonstrated that arterial baroreflex sympathoexcitation due to baroreceptor unloading is attenuated in near-term pregnant compared with nonpregnant rats (43,51). In response to a hypotensive challenge, fos expression is less in pregnant compared with nonpregnant rats, suggesting that neuronal activation of the RVLM during baroreceptor unloading is suppressed in pregnant rats (17).…”
Section: Discussionmentioning
confidence: 93%
“…However, arterial baroreflex sympathoinhibitory responses are well maintained (14) or augmented (43,51) in pregnant rats. Although adaptation of afferent baroreceptor discharge during prolonged pressure stimuli (10 min) appears to be more pronounced in pregnant rats (33) when afferent arterial baroreceptor discharge is assessed by using methods similar to those used in the above-mentioned baroreflex studies, the gain of arterial baroreceptor afferent discharge is not altered by pregnancy (33,43). Therefore, it is likely that alterations in central autonomic integration contribute to the suppressed baroreflex sympathoexcitation that has been reported in pregnant animals.…”
mentioning
confidence: 93%
See 2 more Smart Citations